Analysis of the Quiet Quitting Phenomenon with Work Engagement and Job Satisfaction as mediators, Study of Employees in Indonesia Banking Industry - Melissa Gilbert Sitorus; Riani Rachmawati (Green Publisher Indonesia, 2024)
The phenomenon of quiet quitting has significantly captured global attention across various industries in recent years. Quiet quitting refers to a form of employee disengagement characterized by limiting their efforts to meeting minimal expectations and avoiding additional tasks or responsibilities beyond what is explicitly required. This behavior impacts organizational performance, workplace dynamics, and employee well-being. When employees silently disengage from full involvement in their work, organizations may experience decreased productivity, hindered teamwork dynamics, and challenges in retaining top talent. This research aims to analyze the determinant factors in the quiet quitting intention phenomenon, mediated by work engagement and job satisfaction. Data were collected through a questionnaire and analyzed quantitatively from 405 employees of a banking sector company in Indonesia using purposive sampling and analyzed with Partial Least Square-Structural Equation Modeling (PLS-SEM) using Smart PLS. By understanding these signs, organizations can early detect quiet quitting intention behaviors and take appropriate steps to determine the necessary actions to address the underlying issues of quiet quitting behavior.